Risk factors, urodynamic characteristics, and distress associated with nocturnal enuresis in overactive bladder -wet women - Kuan Chong Ng; Jeff Shih-Chieh Chueh; Shang-Jen Chang (Scientific Reports)
Abstract Patients with overactive bladder syndrome-wet (OAB-wet) experience urgency urinary incontinence, particularly urinary frequency and nocturia. Nocturnal enuresis (NE) is less addressed among OAB-wet patients. The study evaluated the prevalence of NE, lower urinary tract symptoms (LUTS), urodynamic factors, and social factors in OAB-wet patient. Over three years, adult women with urgency urinary incontinence were enrolled. A comprehensive questionnaire, including baseline characteristics, LUTS, fatigue, stress, and partner relationship was completed by the participants. NE was defined as complaint of intermittent incontinence that occurs during the main sleep period. Urodynamics was performed on every patient to assess bladder function. Of 203 OAB-wet patients (age: 64.45 years), 46.4% had NE. Patients with NE had higher scores of intermittency, slow stream, straining, hesitancy, post micturition dribble, nocturia, and stress urinary incontinence than non-NE. NE patients had a more parity numbers, diuretic, hypnotic, and prokinetic use, and smoking. NE patients more likely reported fatigue, anxiety, and distress. Urodynamic studies revealed more detrusor overactivity, detrusor underactivity, and low bladder compliance in NE patients. In conclusion, OAB-wet women with NE had more detrusor overactivity, detrusor underactivity, and a lower compliance bladder on urodynamic studies than those without NE. NE impacts the patients’ life in aggravating fatigues, anxiety, and distress in OAB-wet women.